Prosobranch and shelled opisthobranch molluscs from Store Ekkerøya, Varangerfjorden (northern Norway) - Thierry Backeljau; Marc De Meyer; Luc Janssens; Rudy Proesmans (Fauna Norvegica)
Forty-one prosobranch and six shelled opisthobranch species were collected at Store Ekkerøya (70°05'N., 30°08'E.). Four of these are published for the first time from Varangerfjorden (Helcion pellucidum, Lacuna crassior, Onoba semicostata and Retusa truncatula). Remarks are given on Littorina obtusata s.l., Littorina saxatilis s.l., Alvania mighelsi and Oenopota simplex.